Idealisme Politik Generasi Milenial (Optimisme dan Pesimisme dalam Arah Baru Demokrasi Indonesia) - Rahmat Affandi; Katimin, Katimin (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2025)
Elections are a concrete manifestation of the implementation of democracy in Indonesia, where the participation of the younger generation, especially the millennial generation, is a crucial aspect in determining the direction of the nation's future. However, the emergence of a tendency towards apathy and pessimism towards politics among millennials raises concerns about the quality of democracy in the future. This study aims to understand how the political idealism of the millennial generation, both optimistic and pessimistic, affects their level of political participation. This study highlights the importance of political education as a means to increase awareness and sensitivity of the younger generation to social and political issues. This study uses a qualitative approach with a descriptive type of research, where data is collected through an in-depth understanding of a phenomenon with interviews, online participant observation and analysis of social media upload documents, this study seeks to explore millennial perceptions of politics and the role of social media in shaping their political culture. The results of the study show that millennial attitudes towards politics are greatly influenced by educational factors, personal experience, and trust in the political system. In addition, social media plays a significant role in influencing their views and levels of political participation, both positively and negatively. More effective political education is needed to encourage active participation of millennials in Indonesian democracy.